Supervisory Control and Data Acquisition (SCADA) System for Sedimentation Automation in Water Treatment Plant Using Schneider Modicon M221 Programmable Logic Controller - Hamidi, Eki Ahmad Zaki; Rahmawati, Raisa; Effendi, Mufid Ridlo (Jurnal Teknik Elektro Indonesia, 2025)
This research discusses the application of the Supervisory Control and Data Acquisition (SCADA) System in the sedimentation automation process in water treatment plants. SCADA is used to monitor and control various critical parameters in the sedimentation process, increasing the efficiency and accuracy of water treatment. This system is implemented using a Programmable Logic Controller (PLC), the Schneider Modicon M221, which functions as the main controller. The Schneider Modicon M221 PLC was chosen because of its reliability in managing automation processes and its ability to integrate with SCADA systems. The results of this implementation show significant improvements in process control, operational efficiency, and real-time monitoring, all of which contribute to the improved quality of treated water. And sludge removal in the sedimentation system occurs when the sensor reads that the water has a turbidity value equal to 14 NTU.